Effect of Row Circle Method and Variety of Hybrid Corn on Yield of Corn (Zea mays L) - Use Etica; Mahmudah Hamawi (Gontor AGROTECH Science Journal, 2016)
Corn yield improved by genetic improving, plant population and fertilizer. The experiment aims to knowing the effect off row circle planting method and hybrid corn variety toward population and yield of corn. The experiment was conducted on August- November 2015 in Siman, Ponorogo, altitude 140 amsl and textured clay grumosol soil types. The experiment was a factorial experiment in a complete block randomized design with two factor and three replications. The first factor was hybrid corn varieties (Bisi-18, NK-7328, Pertiwi-3, and Pioneer-27). The second factor was row circle planting method (single manner with interval planting of 60x40x20 cm; row circle planting method with interval planting of 60x100 cm and 100x50x50 cm). The result showed not significantly interaction between row circle planting method and hybrid corn varieties with respect to population total and corn yield. Row circle planting method with interval planting 100x50x50 cm increased plant population about 164.413 plants/ha and significantly different with single manner with interval planting of 60x40x20 cm (62,881 plants/ha) and row circle planting method with interval planting 60x100 cm (136,774 plants/ha). Hybrid corn varieties was not significantly increased plant population. Pioneer-27 variety of hybrid corn produced weight of wet corn logs by 17,22 ton/Ha and significantly different with Bisi-18, NK-7328 and Pertiwi-3. Hybrid corn varieties was not significantly affects to increasing produce of dry corn kernels. Variety of Pioneer-27 produced dry corn kernels 7,28 ton/ha and was not significantly different with varieties of Bisi-18, NK-7328, and Pertiwi-3. Variety of NK-7328 had percentage weight of wet corn logs into dry corn kernels as big as 55,38% bigger than varieties of Bisi-18, Pertiwi-3 and Pioneer-27.